Novel triterpenoid pyrones, phthalimides and phthalates are selectively cytotoxic in CCRF-CEM cancer cells - Synthesis, potency, and mitochondrial mechanism of action - Kazakova, Anna; Frydrych, Ivo; Jakubcová, Nikola; Pokorný, Jan; Lišková, Barbora; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Urban, Milan (European journal of medicinal chemistry, 2024)
A series of triterpenoid pyrones was synthesized and subsequently modified to introduce phthalimide or phthalate moieties into the triterpenoid skeleton. These compounds underwent in vitro cytotoxicity screening, revealing that a subset of six compounds exhibited potent activity, with IC50 values in the low micromolar range. Further biological evaluations, including Annexin V and propidium iodide staining experiment revealed, that all compounds induce selective apoptosis in cancer cells. Measurements of mitochondrial potential, cell cycle analysis, and the expression of pro- and anti-apoptotic proteins confirmed, that apoptosis was mediated via the mitochondrial pathway. These findings were further supported by cell cycle modulation and DNA/RNA synthesis studies, which indicated a significant increase in cell accumulation in the G0/G1 phase and a marked reduction in S-phase cells, alongside a substantial inhibition of DNA synthesis. The activation of caspase-3 and the cleavage of PARP, coupled with a decrease in the expression of Bcl-2 and Bcl-XL proteins, underscored the induction of apoptosis through the mitochondrial pathway. Given their high activity and pronounced effect on mitochondria function, trifluoromethyl pyrones 1f and 2f, and dihydrophthalimide 2h have been selected for further development.
Keywords: pyrony; apoptóza; Cell Line, Tumor; Mitochondria; Membrane Potential, Mitochondrial; Apoptosis; Neoplasms; nádory; DNA; Antineoplastic Agents; protinádorové látky; mitochondrie; triterpeny; ftalimidy; membránový potenciál mitochondrií; Phthalimides; Pyrones; Phthalic Acids; Triterpenes; kyseliny ftalové; nádorové buněčné linie